2022
DOI: 10.1186/s12889-022-12914-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pentavalent and measles vaccination dropouts among children aged 12–23 months in The Gambia

Abstract: Background Every year, vaccination averts about 3 million deaths from vaccine-preventable diseases (VPDs). However, despite that immunization coverage is increasing globally, many children in developing countries are still dropping out of vaccination. Thus, the present study aimed to identify determinants of vaccination dropouts among children aged 12–23 months in The Gambia. Methods The study utilized cross-sectional data obtained from the Gambia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
6
12
1
Order By: Relevance
“…This shows that the likelihood of defaulting from completion of child vaccination was greater among mothers/caregivers residing in urban areas across all antigens, in the wake of rapid urbanization in recent years. This study was consistent with studies conducted in other parts of the world that revealed a failure to cater to the urban poor and slum population, and this is considered as an obstacle to achieving complete vaccination [11,26,[31][32][33]. A possible explanation of these findings may be the loss of access to health facilities in urban slums and the lack of advice regarding the benefits of child vaccination that causes mothers/caregivers to default from child immunization.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This shows that the likelihood of defaulting from completion of child vaccination was greater among mothers/caregivers residing in urban areas across all antigens, in the wake of rapid urbanization in recent years. This study was consistent with studies conducted in other parts of the world that revealed a failure to cater to the urban poor and slum population, and this is considered as an obstacle to achieving complete vaccination [11,26,[31][32][33]. A possible explanation of these findings may be the loss of access to health facilities in urban slums and the lack of advice regarding the benefits of child vaccination that causes mothers/caregivers to default from child immunization.…”
Section: Discussionsupporting
confidence: 89%
“…At present, there is 93.6% coverage for DPT1 and 86.7% coverage for DPT3 in India. A handful of studies have investigated the reasons behind dropout after the first dose of DPT or oral polio vaccine (OPV) globally, albeit within a very limited scope [24][25][26][27]. Therefore, there is a need to explore the factors contributing to the dropout cases from vaccination in India from the time of first vaccine is scheduled (BCG) to the last vaccine in the schedule (MCV1) which is given in the first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis showed that the dropout of Pentavalent 1-3 was 26.7%. The dropout rate of pentavalent 1-3 is almost similar with the pooled prevalence of vaccination dropout, which was reported to be 26.06% in sub-Saharan Africa (Natnael et al, 2022) and Much higher compared to the systematic reviews and meta-analyses that reported 7.0% and 4.0% among children aged 12-23 months, respectively, in Gambia (Peter et al, 2022); and the dropout rate of Pentavalent 3 is lower compared to the studies done in Nepal (30.4%) (Supri and Attarkhel, 2020).…”
Section: Determinants Of Immunization Dropoutsupporting
confidence: 72%
“…A wealth quintile is a measure of the relative economic status of a household within a population, usually divided into ve groups from poorest to richest (Ntenda et al, 2022).. This study depicted immunization dropout decreases as the level of wealth quintile increases from poorer to richer compared to those in the poorest wealth quintile category.…”
Section: Determinants Of Immunization Dropoutmentioning
confidence: 80%
“…Additionally, in this article, we assessed the association of vaccination with conflict in an exploratory and covariate selection procedure for which the association was statistically weak. Reaching people in fragile and conflict-affected settings is documented [12,58] but will require an expanded understanding of other population-level contextual, vaccine demand and uptake, cultural factors, socio-demographic factors and supply-side factors of vaccine delivery not considered here [59][60][61].…”
Section: Discussionmentioning
confidence: 99%